Molecular mechanisms of resistance and new therapeutic approaches in the treatment of colorectal cancer - a review of the literature - Janeczek, Maksymilian; Plewniok, Julia; Partyka, Maria; Wójcik, Julia; Kantor, Karolina Kinga; Cholewa, Marcin; Szymańska, Wiktoria Maria; Jaglarz, Karolina; Kuca, Maciej; Pamuła, Kacper Wojciech (Journal of Education, Health and Sport, 2024)
CRC occupies one of the leading positions among gastrointestinal malignancies and is a significant problem in Europe since it is the third most frequently diagnosed cancer. Recent developments in diagnostic techniques have led to higher chances of early diagnosis and survival; nevertheless, CRC is highly likely to relapse in the survivorably younger individuals. The importance of the current chemotherapy treatment and potential key therapeutic targets are identified in this review so that the molecular alterations causing drug resistance in CRC can be studied.Current literature formed the basis of this review by reviewing the molecular processes that underlie CRC, with emphasis on the mutational alterations in genes such as SENP1, KRAS, APC, TP53, and BRAF that play critical roles in CRC and resistance to treatment. Chemotherapy for CRC, targeting therapies, and immuno therapies have been discussed particularly with reference to their effectiveness for treatment and overcoming resistance.Genomic alterations in some important genes are involved in the onset of CRC and also determined the response to therapies. The KRAS mutations are associated with the resistance to EGFR inhibitors; however, BRAF mutations require BRAF/MEK inhibitors. Lack of MMR system SSR as a trigger for MSI-H status suggests a better response to immunotherapies. In addition, new molecules including SENP1, which involved the DNA repair pathway, and combination using CDK4/6 inhibitors are currently under development to overcome resistance and enhance the patients’ benefits.Colorectal cancer is still a problem, primarily because of its genetic character and high rates of recurrence. Even though chemotherapy and targeted therapies offer helpful results, the problem of resistance stands in the way. Subsequent studies should aim at symptomatic treatment outcomes and combine different drugs in order to enhance long-term treatment outcomes.